Pelatihan Pembuatan Jamu Milenial Berbahan Pangan Lokal Kalimantan Daun Kalakai (Stenochlaena palustris) pada Ibu PKK Desa Sungai Besar Kabupaten Banjar: Training in Herbal Medicine Production from Kalakai Leaves to Prevent Stunting for PKK Mothers in Sungai Besar Village, Banjar Regency - Wati, Helmina; Susiani, Eka Fitri; Effendi, Ibrahim Rully; Triyasmono, Liling; Nugroho, Agung; Rizki, Muhammad Ikhwan (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Stunting is defined as a chronic nutritional problem caused by a lack of adequate nutritional intake over an extended period. Iron is a vital component for cellular growth and development, as well as immune system function. The solution to overcoming iron deficiency is to consume highly nutritious foods, such as meat and green leafy vegetables. One such food is the kalakai plant. The Sungai Besar Village, Banjar Regency, is characterized by an abundance of natural resources that flourish in a wild state. Among these is the kalakai plant (Stenochlaena palustris (Burnm. F.) Bedd.), which is notable for its high iron content. The plant is employed solely as a vegetable. The objective of this community service activity is to enhance the competencies and understanding of PKK mothers in Sungai Besar Village about the diversification of processed kalakai plant products into millennial herbal medicine products. The methodology employed involved the preparation of the field, the counseling of the potential of kalakai leaves, and the training in the production of diversified kalakai leaves into millennial herbal medicine. The results and conclusions of this activity demonstrated an increase in knowledge of 85% and an 89% increase in the skills of PKK mothers in Sungai Besar Village in the diversification of kalakai leaves for the production of millennial herbal medicine derived from local Kalimantan plants.